2014
DOI: 10.5539/jas.v6n10p176
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cowpea Genotypes for Virus Resistance Under Natural Conditions in Uganda

Abstract: Cowpea (Vigna unguiculata L. Walp) is an important grain legume in most parts of Sub Saharan Africa. However, viral diseases are a major limiting production factor causing significant yield losses. An experiment was conducted to evaluate the reaction of 105 different cowpea genotypes to viral infection in different agro-ecological zones of Uganda. The aim was to identify genotypes that could serve as sources of resistance to virus infection. Virus infection in these experiments occurred naturally through insec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…In this study, genotypes Apagbaala, UCC-366, UCC-489, UCC-490, UCC-497, UCC-514 and UCC-523 with low disease severity in terms of AUDPC and low final severity scores may offer single or multiple virus resistance, which is comparable to previous work (Essandoh et al, 2017), where these nine cowpea genotypes were found to exhibit field resistance. This finding also corroborates the report by Mbeyagala et al (2014) when they screened 105 cowpea genotypes for resistance against viral infection under natural condition in Uganda. The ELISA serology revealed that genotype UCC-366 that also exhibited field resistance was coinfected with CMV, CPSMV and CMV (Table 5), demonstrating multiple field resistance against these three viral species.…”
Section: Incidence and Severity Of Viruses On Selected Cowpea Genotypessupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, genotypes Apagbaala, UCC-366, UCC-489, UCC-490, UCC-497, UCC-514 and UCC-523 with low disease severity in terms of AUDPC and low final severity scores may offer single or multiple virus resistance, which is comparable to previous work (Essandoh et al, 2017), where these nine cowpea genotypes were found to exhibit field resistance. This finding also corroborates the report by Mbeyagala et al (2014) when they screened 105 cowpea genotypes for resistance against viral infection under natural condition in Uganda. The ELISA serology revealed that genotype UCC-366 that also exhibited field resistance was coinfected with CMV, CPSMV and CMV (Table 5), demonstrating multiple field resistance against these three viral species.…”
Section: Incidence and Severity Of Viruses On Selected Cowpea Genotypessupporting
confidence: 90%
“…Managing these viruses with insecticides is not effective because they are transmitted by several insect species in a non-persistent manner (Umaharan et al, 1997). The most economical, practicable and effective method of reducing crop losses due to viral infection is through the use of resistant varieties (Taiwo, 2003;Mbeyagala et al, 2014). Development of resistant varieties against different type and strain of viruses entails screening of germplasm in a particular agro-climate for identification of resistance to the particular strain prevailing in that region.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Yan and Rajcan (2002), Yan and Tinker (2006) and Blanche et al (2007) also reported on discriminative power of GGE biplots. Though none of the genotypes was completely immune to virus infection as previously reported by Mbeyagala et al (2014), the identified resistant genotypes are potential sources of resistance for germplasm improvement, as well as cultivation if preferred by farmers.…”
Section: Andsupporting
confidence: 55%
“…However, there have been no targeted studies on cowpea germplasm reaction to flower bud thrips in Uganda and farmers are still growing the susceptible cultivars (Asio et al, 2005). Studies under natural infestation indicated possible existence of thrips resistant lines among the local cowpea cultivars (Karungi et al, 2000;Mbeyagala et al, 2014). The objective of this study was to identify the cowpea lines that are resistant to flower thrips for the development of sustainable thrips management strategies.…”
Section: Introductionmentioning
confidence: 99%